'But I am a kid': Optimizing adolescence in Oshii Mamoru's The Sky Crawlers. Issue 1 (1st April 2016) - Nelson, Lindsay
Oshii Mamoru's 2008 film The Sky Crawlers imagines a world in which cloned adolescents (Kildren) are made to fight staged aerial battles for the entertainment of the TV-viewing public. This article uses the narrative and visual aesthetic of The Sky Crawlers to examine what it means to be an adolescent, a killer, and a human being in a world where reality and spectacle have become indistinguishable, and where both the bodies of young people and the very idea of adolescence (as a liminal state defined by a lack of experience in and wisdom about the world) have been commodified by corporations. The existence of the Kildren and the world they live in is made all the more vivid through the visual framework of anime, which has a long history of using contrasting drawing styles (hyper-real for machines, handdrawn for humans). This framework allows The Sky Crawlers to re-imagine the idea of 'deathlessness' in anime and manga, with the hand-drawn bodies of Kildren characters emphasizing the impermanent, recyclable nature of their existence. The film points to a world in which spectacle reigns supreme, and everything – bodies, emotions, the very concept of adolescence – has the potential to be optimized to enhance that spectacle.